The Influence of School Principals' Transformational Leadership Style on Teacher Performance - Indahsari, Tri; Burhanuddin, Burhanuddin (Proceedings Series of Educational Studies, 2025)
This study examines the impact of transformational leadership style by school principals on teacher performance. Using a systematic literature review (SLR) approach, this research analyzes studies published over the past ten years (2014-2024) sourced from Springer, Taylor & Francis, and other relevant databases focused on Indonesia. The review follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, involving identification, screening, and inclusion steps, resulting in 20 articles selected for final analysis. The findings indicate that transformational leadership positively influences teacher performance by increasing motivation, inspiring teachers, and fostering a sense of responsibility in their tasks. Principals who adopt a transformational leadership style can create a positive work environment, provide clear direction, and motivate teachers to enhance their competencies and teaching performance, ultimately leading to improved student outcomes and more effective achievement of educational goals. Additionally, transformational leadership strengthens collaboration among school staff, fosters a culture of learning, and enhances teacher professionalism. This study emphasizes that the quality of school leadership plays a crucial role in improving teacher performance, and recommends that school principals continuously develop their transformational leadership skills to motivate and inspire their staff. By doing so, principals can create a more effective school environment and contribute to achieving the vision and mission of education.